From Alfvén waves to kinetic Alfvén waves in an inhomogeneous equilibrium structure. Issue 2 (27th February 2016) - Pucci, F.; Vásconez, C. L.; Pezzi, O.; Servidio, S.; Valentini, F.; Matthaeus, W. H.; Malara, F.
Abstract: Kinetic Alfvén waves are believed to primary form fluctuations in a hydromagnetic turbulence at scales of the order of the ion inertial length. We study a model where an initial Alfvén wave propagates inside an equilibrium structure which is inhomogeneous in the direction perpendicular to the equilibrium magnetic field. In a previous paper this situation has been considered in a particular configuration where the initial wave vector is parallel to the magnetic field and the wave is polarized perpendicular to the inhomogeneity direction. Here we consider other configurations, with a different polarization and possible initial oblique propagation. We employ numerical simulations, using both a Hall‐magnetohydrodynamics and a Hybrid Vlasov‐Maxwell model. Results show that in all the considered cases the time evolution leads to the formation of kinetic Alfvén waves within the inhomogeneity regions, which are identified by a comparison with analytical linear theory results. Then, in this context the formation of kinetic Alfvén waves seems to be a general phenomenon which could be also extended to more complex situations, like turbulence. Kinetic simulations show that kinetic Alfvén waves modify the ion distribution function, generating temperature anisotropy of both parallel and perpendicular to the local magnetic field as well as particle beams aligned along the local magnetic field. These results could be relevant both in the solar corona and in large‐scale structures of the solar wind, where Alfvénic fluctuations are present along with large‐scale inhomogeneities. Key Points: Mechanisms to produce kinetic Alfvén waves in pressure‐balance structures Linear and nonlinear simulations of propagating Alfvén waves Kinetic effects due to the propagation of kinetic Alfvén waves